Implikasi Gaya Audit Terhadap Komparabilitas Laporan Keuangan - Butar-Butar, Sansaloni (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
Prior studies show that earnings attributes were influenced by characteristics of audit firms hired by clients. Big Four audit firms were reported to have developed working rules to assess accounting standards used by firms in preparing financial reports and consistently applied these working rules across all clients. Unique audit methodology and procedures create audit style that belongs to particular audit firm, especially Big Four audit firms. As a consequence, financial statements audited by the same Big Four audit firms experience similar audit processes and show higher consistency than those of firms audited by different Big Four audit firms. Applying the same audit style is expected to increase financial statements comparability between two companies audited by the same Big Four audit firms. Therefore, a pair of companies audited by the same audit firms is predicted to have more comparables earnings than audited by different Big Four audit firms. Results supported the hypothesis that audit style improves financial statements comparability of firms audited by same Big Four audit firms.